Effects of Environmental Pollution on Public Health in Dhaka City, Bangladesh - Nahar, Najmun; Mahiuddin, Sanjia; Hossain, Md. Faruk (Sriwijaya Journal of Environment, 2024)
Dhaka City is the most polluted city in Bangladesh compared to other cities. Rapid urbanization and uncontrolled population growth are creating mismanagement of urban amenities in this city and concurrently generating air, water, land, noise pollution, etc., which affects public health. Therefore, the paper attempts to represent the status of the effects of significant environmental pollution on public health in the study area. The study was mainly based on primary data, although secondary data was used.  Four hundred respondents who suffered from health problems caused by environmental pollution were randomly selected and interviewed from jointly ten zones of Dhaka North City Corporation and Dhaka South City Corporation using a semi-structured questionnaire. The study found that the health of 90% of respondents was affected by air pollution, 60% by water pollution, 55% by noise pollution, and only 2% by soil pollution in the study area, considering multiple response criteria. Air, water, and noise pollution had a significant health impact on the respondents, considering all age groups except for soil pollution. The study's outcomes strongly support the need for more analysis to reduce the effects of pollution and provide a safe and healthier environment for the people of Dhaka City.